The Effect of Firm Size and Firm Age on Sustainability Reporting and The Impact on Earnings Management - Fani Fadilah; Lia Uzliawati; Windu Mulyasari (Jurnal Riset Akuntansi Terpadu, 2022)
This study aims to analyze the effect of firm size and firm age on sustainability reporting and its impact on earnings management. The antecedent variable used in this study is firm size measured by Ln asset total and firm age measured by the result of research year data minus the year the company was founded. The independent variable used in this study is sustainability reporting measured by Global Reporting Initiative (GRI). Variable dependent used in this study is earnings management measured by discretionary accrual modified jones. The population of this research is mining companies listed on Indonesia Stock Exchange in 2015-2019. Based on the purposive sampling method, the sample chosen in this research is 14 companies with total sample of 70 data. This study used multiple linear regression analysis using SPSSv25 software. The result of this study showed that firm size has a positive impact on sustainability reporting, firm age has a positive impact on sustainability reporting, SR economic dimension has a positive impact on earnings management, SR environmental dimension has a negative impact on earnings management. However, SR social dimension doesn’t affect earnings management.